Payment scenario in the Malaysian construction industry prior to ClPAA - Azman, Mohamed Nor Azhari; Dzulkalnine, Natasha; Abd Hamid, Zuhairi; Mohamad Kamar, Kamarul Anuar; Mohd Nawi, Mohd Nasrun (2013)
This report is literature reviews undertaken to re-establish the state of payment problems in the Malaysian construction industry.The findings from this study will be used as a guide for further survey to measure the situation of the payment problems before the enactment of Construction lndustry Payment and Adjudication Act (CIPAA).There are journals selected to be included in this study.The purposes of the journal were to discover the financial issues of late and non-payment problem related to the causes of delay in construction projects. Most of the research in the journals was carried out by adopting a combination of document analysis, law cases and review of act and statue.The possible solution to overcome the issue to the late and non-payment in construction projects were also highlighted in the journals. Based on the discussion, this research gives a general view and provides a comprehensive result of the "Payment Scenario in the Malaysia Construction lndustry Prior to CIPAA".The result in this paper covered the factors contributed to the late and non-payment problem in construction industry, impact of late and non-payment and also the possible solution towards late and non-payment problem in construction industry.